Review and Comparison of Sensorless Techniques to Estimate the Position and Speed of PMSM - Yusnida Ahmad Tarmizi; Kasrul Abdul Karim; S. Azura Ahmad Tarusan; Auzani Jidin (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
Sensorless technique becomes popular nowadays in electrical drive applications specificially for AC motor drive. It is applied to determine and estimate the rotor position especially for PMSM motor. This paper presents the comparison sensorless technique to determine and estimate the position and rotor of PMSM motor. PMSM motor is widely used in industrial and automation due to its high performance motor drive. However, the location of PMSM motor in humidity and harsh environment causing the accuracy of motor is inaccurate due to deterioration of position sensor . Therefore, many sensorless techniques have been proposed by previous researchers in order to solve the problem. This paper presents the review of several categories; Model Based Method, Saliency Based Method and Signal Injection, and Artificial Intelligence Based Estimator. In addition, sensorless techniques on each category have been compared and described in terms of their advantages and disadvantages.